Silver Nanoparticles Alter Microtubule Arrangement, Dynamics and Stress Phytohormone Levels - Jindřiška Angelini; Ruslan Klassen; Jitka Široká; Ondřej Novák; Kamil Záruba; Jakub Siegel; Zuzana Novotná; Olga Valentová (Plants, 2022)
The superior properties of silver nanoparticles (AgNPs) has resulted in their broad utilization worldwide, but also the risk of irreversible environment infestation. The plant cuticle and cell wall can trap a large part of the nanoparticles and thus protect the internal cell structures, where the cytoskeleton, for example, reacts very quickly to the threat, and defense signaling is subsequently triggered. We therefore used not only wild-type Arabidopsis seedlings, but also the glabra 1 mutant, which has a different composition of the cuticle. Both lines had GFP-labeled microtubules (MTs), allowing us to observe their arrangement. To quantify MT dynamics, we developed a new microscopic method based on the FRAP technique. The number and growth rate of MTs decreased significantly after AgNPs, similarly in both lines. However, the layer above the plasma membrane thickened significantly in wild-type plants. The levels of three major stress phytohormone derivatives—jasmonic, abscisic, and salicylic acids—after AgNP (with concomitant Ag+) treatment increased significantly (particularly in mutant plants) and to some extent resembled the plant response after mechanical stress. The profile of phytohormones helped us to estimate the mechanism of response to AgNPs and also to understand the broader physiological context of the observed changes in MT structure and dynamics.